Translation assessment of Qur'anic & prophetic intertextuality with reference to Maḥfūẓ's Cairo trilogy - Muhammed, Essam Taher; Abdulrahman Al-Qazaz, Abdulrahman A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Egyptian novelist Najīb Maḥfūẓ has proved himself to be a genius author at incorporating a variety of academic and intercultural sources in his works. He uses many forms of Islam-related references, such as the Qur'anic and Prophetic ones, to convey his intended meanings. In the present study, we attempt to assess the translation of Qur'anic and prophetic intertextuality in Maḥfūẓ's "Cairo Trilogy " using the criteria proposed by Larson's Model(1984). This study follows a qualitative approach to analysis,i.e., the data is not in the form of numbers but in the form of texts. This study aims to discover the tactics utilized in translating Arabic Qur'anic and prophetic intertextuality into English, as well as to identify the obstacles faced by the subject translators and the reasons behind such challenges. The study concludes that irrespective of what method the translators adopt to translate Qur'anic and prophetic intertextuality, their religious and cultural background seriously influences the output of the translation process.